Nursing actions in human milk banks in times of COVID-19 - Marchiori,Giovanna Rosario Soanno (2020)
ABSTRACT Objective: To analyze the actions of the Human Milk Banks coordination to favor the continuity of breastfeeding in the COVID-19 pandemic. Methods: Descriptive study, of qualitative approach, with theoretical-methodological reference of Pierre Bourdieu. Data collection was done through interviews between March and April, with five coordinations and results organized by thematic analysis. Results: Two categories were produced: the actions of strategies for the maintenance of Human Milk Banks services by digital means as a way to ensure social distancing and breastfeeding in times of pandemic of the new coronavirus; and the actions of promotion, protection and support in strategies for maintenance of breastfeeding during the pandemic. Final considerations: The benefits of breastfeeding outweigh any potential risks of transmission of the new coronavirus. The importance of systematic nursing practices in the quality and safety of the process of Protection, Promotion and Support of Breastfeeding is evident.